Ergon as a Political Category of Human Being: An Interpretation of Nicomachean Ethics 1097b2-1098a2 - Ciruzzi, Luciano (2025)
This paper presents an interpretation of the passage in which Aristotle introduces the first two premises of the ergon argument (EN 1097b22-1098a2). It aims to demonstrate, first, that in these few lines Aristotle provides two examples of reasoning that can be seen, due to their form and pedagogical function, as inductive. At the same time, second, I argue that these inductions are built on an apparently unsuccessful move: namely, presenting propositions concerning one genus of beings and then drawing a conclusion about another genus of beings. To address this apparent transgression, I contend that throughout the passage it is presupposed that the ergon is a necessary property of all individuals who form part of a political community. Thus, the object of the explanation (i.e., the ergon) can be understood as a property of human beings as such qua political animals. From this perspective, the apparent argumentative difficulties of the passage are resolved.